Comprehensive or Implementable? A Review of Y. Bouchamma, M. Giguère and D. April’s, Pedagogical Supervision Standards: A Conceptual Framework - Hunter, Darryl (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2021)
I argue in this book review that the authors have created a readily implementable framework for school principals' in their instructional supervision tasks, by virtue of not attempting to become comprehensive.